Assessing Sustainability of Higher Education Institutions: the University Sustainability Assessment Framework - Petya Dankova (Икономика и компютърни науки, 2024)
In recent decades, there has been a notable increase in the discourse surrounding the conceptualisation of sustainable development and the methodologies by which it can be measured and achieved. The United Nations 2030 Agenda for Sustainable Development has been adopted, and 17 corresponding Sustainable Development Goals have been established. Nevertheless, the global community remains a considerable distance from attaining sustainable development. Universities have the potential to play a pivotal role in addressing this challenge, given their position as institutions responsible for preparing future leaders and decision-makers. However, a significant challenge lies in the design and implementation of effective instruments for evaluating the extent to which academic institutions advance sustainable development. Accordingly, the aim of this article is to examine the assessment tools employed for evaluating universities' contributions to sustainable development, with a particular focus on the University Sustainability Assessment Framework (UniSAF) indicators.